Medium Chain Triglycerides Modulate the Ketogenic Effect of a Metabolic Switch - Vandenberghe, Camille; St-Pierre, Valérie; Fortier, Mélanie; Castellano, Christian-Alexandre; Cuenoud, Bernard; Cunnane, Stephen C. (Frontiers in Nutrition, 2020)
Ketones provide an alternative brain fuel and may be neuroprotective in older people. Little is known of how to optimize the ketogenic effect of C8:0–C10:0 medium chain triglyceride supplement (kMCT). Metabolic switching (MS) from glucose to ketones as a fuel may have metabolic benefits but has not been extensively studied in humans. The objective of the present study was to use an 8 h metabolic study day protocol to assess the influence of typical components of MS, including a kMCT supplement, low-carbohydrate meal and meal timing, on blood ketones, glucose, insulin and free fatty acids (FFA). In one test, the effect of age was also investigated. Over the 8 h metabolic study day, two 10 g doses of the kMCT increased the plasma ketone response by 19% while reducing overall glycemia by 12% without altering insulin or FFA levels. Moreover, a single early meal (breakfast but no lunch) potentiated the ketogenic effect of MS over 8 h, compared to a single delayed meal (lunch but no breakfast). Age and the low carbohydrate meal did not affect the ketones response. We conclude that an 8-h test period can be used to assess metabolic changes during short-term MS. kMCT provide a robust short-term increase in ketones and might enhance the metabolic effectiveness of short-term or intermittent fasting as a component of MS.